Afganistan İslam Cumhuriyeti'nde yargı teşkilatı - Sadat, Khatera (My University, 2019)
Bir ülkedeki yargı teşkilatı, o ülkede adaletin sağlanması ve yargı kuvvetinin yerine getirilmesi için faaliyet gösteren örgüttür. Bu itibarla, yargı teşkilatını analiz etmek, o ülkenin hukukî yapısı ile ilgili çok önemli bilgiler sunmaktadır. Bu çalışmanın hedefi 2002’de kurulan Afganistan İslâm Cumhuriyeti’nin yargı teşkilatını ayrıntılı bir biçimde ele almak ve bu teşkilatı geliştirecek bazı teklifler sunmaktır. Türkçe, Arapça, Farsça ve İngilizce kaynaklara dayanan bu çalışmada Afganistan İslâm Cumhuriyeti Yargı Teşkilatı; iki genel bölüm şeklinde ele alınmıştır.

The judicial organization in a country is the most important unit that operate for justice in that country. In this respect, analyzing the judicial organization provides important information about the legal structure of that country. The aim of this study is to examine in detail the judicial organization of the İslamic Republic of Afghanistan, which was established in 2002 and to make some proposals to improve this organization. This study is based on Turkish, Arabic, Persian and English sources and discussed the Judicial Organization of the İslamic Republic of Afghanistan; in two general sections.
Keywords: Afganistan; Afghanistan; Courts; Hukuk Sistemi; Islam; Islamic law; İslam hukuku; İslâm Hukuku; İslamic Law; İslamiyet; Judicial Organization; Legal System; Mahkemeler; Modern Hukuk : Afghanistan; Modern Law; Yargı Teşkilatı